Prevalence of chronic pain in Brazil: A systematic review and meta-analysis - Santiago, Bruno Vitor Martins; Oliveira, Ana Beatriz Garcez de; Silva, Gabriel Machado Romão da; Silva, Maxuel de Freitas da; Bergamo, Pedro Ernandes; Parise, Maud; Villela, Nivaldo Ribeiro (Clinics, 2023)
Objective: This review synthesized existing studies on the prevalence of chronic pain in Brazil and its associated factors to produce a recent estimation to guide public health politics. Methods: A search was carried out in the Ovid Medline, Embase, Web of Science, and BVS Regional/Lilacs databases to identify population-based cross-sectional studies from 2005 to 2020, which reported the prevalence of benign chronic pain in Brazil (more than three months). The risk of bias was assessed using design, sample size determination, and random selection as essential issues. Pooled prevalence estimates were calculated for chronic pain in the general and elderly populations. The protocol was registered on Prospero (CRD42021249678). Results: Of the 682 identified, 15 macheted the authors’ inclusion criteria. Chronic pain prevalence in the general adult population ranged from 23.02% to 42.33% (pooled estimate 35.70%, 95% Cis 30.42 to 41.17) and was described as moderate to intense. It was associated with female sex, old age, lower education, intense professional activity, excessive alcohol consumption, smoking, central obesity, mood disorder, and sedentarism. The Southeastern and Southern regions presented a higher prevalence. The prevalence in the elderly population ranged from 29.3% to 76.2% (pooled estimate 47.32%, 95% Cis 33.73 to 61.11). In addition, this population visited doctors more frequently, had more sleep disorders, and was more dependent on daily living activities. Almost fifty percent of both populations with chronic pain reported pain-induced disability. Conclusion: Chronic Pain is highly prevalent in Brazil and associated with significant distress, disability, and poorly controlled.